2017
DOI: 10.1787/ae3a5ce9-en
|View full text |Cite
|
Sign up to set email alerts
|

Understanding variations in hospital length of stay and cost

Abstract: All health Working Papers are now available through the OECD's website at: http://www.oecd.org/els/health-systems/health-working-papers.htm JT03411963 Complete document available on OLIS in its original format This document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…For instance, similar to our results, Gobillon and Milcent have found that differential use of surgical procedures contributed to the substantial regional disparity in AMI mortality in France [14]. In a multi-country analysis, Lorenzini and Marino have found that hospital size and types explain the cross-country variation in efficiency outcomes such as LOS and costs [16]. These studies highlighted the importance of understanding the disparity in healthcare delivery at different geographic levels.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…For instance, similar to our results, Gobillon and Milcent have found that differential use of surgical procedures contributed to the substantial regional disparity in AMI mortality in France [14]. In a multi-country analysis, Lorenzini and Marino have found that hospital size and types explain the cross-country variation in efficiency outcomes such as LOS and costs [16]. These studies highlighted the importance of understanding the disparity in healthcare delivery at different geographic levels.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, our analysis of the geographic disparity of readmission rate is comparable to the research on the variation of hospital performance indicators such as emergency admission mortality [14,65], LOS [16] and hospital resource utilisation [17] in other contexts. For instance, similar to our results, Gobillon and Milcent have found that differential use of surgical procedures contributed to the substantial regional disparity in AMI mortality in France [14].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This paper reports initial findings of empirical analysis aimed at exploring the relationship between the degree of administrative decentralisation across levels of government in health care decision-making and health care spending, life expectancy and hospital costs. This empirical analysis builds on previous analytical research carried out by the OECD Secretariat on "Which policies increase value for money in health care" (Lorenzoni et al, 2018) and on "Understanding variations in hospital length of stay and cost" (Lorenzoni and Marino, 2017), both of which established new methodological tools to analyse health sector performance. The present analysis expands on this earlier work by adding "decentralisation" as a core explanatory variable in the country-level and hospitallevel models, at the request of the Fiscal Network and Joint Network of Senior Budget and Health Officials.…”
Section: Introduction and Main Findingsmentioning
confidence: 99%